PLAYING AT WORK OR WORKING WITH THE GAME: THE PRACTICE OF TEACHING SCHOOL PHYSICAL EDUCATION TEACHER (Fiep Bulletin - online, 2016)
The teacher's pedagogic practice of Physical Education seems playful, once their proposals involve games and attractions that usually participates in exercises to demonstrate the activity or to compose teams. This study makes use of theories of game and work involving education and support necessary to understanding this school practice. Aims to investigate the perception of work and play of a group of teachers of Physical Education before his professional activity. Is justified by the opportunity to contribute to a larger project which aims to research the topic with more breadth and depth, aiming at building a valid knowledge in the area of ??education and work. The results showed that the physical education teacher is perceived working and playing (confused perception) in their professional activity, as were the responses of 17 of 21 whereas the other 4 showed the perception of work, ie, no teacher percebe- it as another player in your classes. As a conclusion it is possible to point out that this group of teachers does not play at work, got the job as the survival activity required and works with the game, considering it as the content of Physical Education.
Keywords: game; work; Physical Education